Difficult airway. Clinical case: Lymphangioma of the neck in a child under one year old (Perioperaciina Medicina, 2019)
The article describes an interesting clinical case of neck lymphangioma in a child under one year, as the cause of difficult airway during surgery. This case deserves the attention of anesthesiologists, surgeons, interns, considering the clinical features, these additional examination methods and features of anesthesia patients. There was emphasized the importance of pre-operative examination of patients, the use of additional tests and examination methods to determine further tactics. Based on this case, it was concluded that each anesthesiologist must have the skills and clearly know the clinical protocols for managing “difficult airway” and predict severe tracheal intubation.
Keywords: difficult airway; neck lymphangioma; tracheal intubation; laryngoscopy; prognostic tests